Idémönster i Karin Neuman-Rahns livsgärning och författarskap : en idéhistorisk-biografisk studie i psykiatrisk vård i Finland under 1900-talets första hälft - Matilainen, Dahly (Åbo Akademis förlag, 1997)
Summary: Patterns of ideas in Karin Neuman-Rahn's life-work and writings - a study of psychiatric care in Finland in the former part of the twentieth century, based on biography and the history of ideas.